SUBDUCTION AND MELTING PROCESSES INFERRED FROM U-SERIES, SR-ND-PB ISOTOPE, AND TRACE ELEMENT DATA, BICOL AND BATAAN ARCS, PHILIPPINES - DuFrane S.A.; Asmerom Y.; Mukasa S.B.; Morris J.D.; Dreyer B.M. (My University, 2006)
We present U-series, Sr-Nd-Pb isotope, and trace element data from the two principal volcanic chains on Luzon Island, developed over oppositely dipping subduction zones, to explore melting and mass transfer processes beneath arcs. The Bataan (western) and Bicol (eastern) arcs are currently subducting terrigenous and pelagic sediments, respectively, which have different trace element and isotopic compositions. The range of (230Th/238U) disequilibria for both arcs is 0.85-1.15; only lavas from Mt. Mayon (Bicol arc) have 230Th activity excesses. Bataan lavas have higher 87Sr/86Sr and lower 143Nd/144Nd than Bicol lavas (87Sr/86Sr = 0.7042-0.7046, 143Nd/144Nd = 0.51281-0.51290 vs. 87Sr/86Sr = 0.70371-0.70391, 143Nd/144Nd = 0.51295-0.51301) and both arcs show steep linear arrays towards sediment values on 207Pb/204Pb vs. 206Pb/204Pb diagrams. Analysis of incompatible element and isotopic data allows identification of a sediment component that, at least in part, was transferred as a partial melt to the mantle wedge peridotite. Between 1% and 5% sediment melt addition can explain the isotopic and trace element variability in the rocks from both arcs despite the differences in sediment supply. We therefore propose that sediment transfer to the mantle wedge is likely mechanically or thermally limited. It follows that most sediments are either accreted, reside in the sub-arc lithosphere, or are recycled into the convecting mantle. However, whole-sale sediment recycling into the upper mantle is unlikely in light of the global mid-ocean ridge basalt data. Fluid involvement is more difficult to characterize, but overall the Bicol arc appears to have more fluid influence than the Bataan arc. Rock suites from each arc can be related by a dynamic melting process that allows for 230Th ingrowth, either by dynamic or continuous flux melting, provided the initial (230Th/232Th) of the source is ?0.6-0.7. The implication of either model is that inclined arrays on the U-Th equiline diagram may not have chronologic significance. Modeling also suggests that U-series disequilibria are influenced by the tectonic convergence rate, which dictates mantle matrix flow. Thus with slower matrix flow there is a greater degree of 230Th ingrowth. While other factors such as prior mantle depletion and addition of a subducted component may explain some aspects of U-series data, an overall global correlation between tectonic convergence rate and the extent of U-Th disequilibria may originate from melting processes. ? 2006 Elsevier Inc. All rights reserved.
Keywords: ISOTOPIC COMPOSITION; MASS TRANSFER; MELTING; SUBDUCTION ZONE; TRACE ELEMENT; URANIUM SERIES DATING; BATAAN; BICOL